DIGITAL MARKETING AND SALES SUPPORT FOR HYDROPONIC MSME GROWTH THROUGH MOBILE BASED E-COMMERCE DESIGN - Frans Sudirjo; Tanti Widia Nurdiani; Yoseb Boari; Kraugusteeliana Kraugusteeliana; Ramdhan Kurniawan (Jurnal Ekonomi, 2023)
This research concentrates on the development of mobile E-commerce to support the growth of micro, small, and medium-sized enterprises (MSMEs) in the hydroponics industry. The primary goal was to develop a responsive and user-friendly mobile application that would enable hydroponic businesses to increase consumer engagement through digital marketing. Observation and data analysis comprised the research method. With the help of the literature review, the user requirements and preferences for a hydroponic industry-appropriate e-commerce system were determined. The e-commerce mobile application incorporates product information, appealing photos and videos, business information, and product details based on data analysis. This study emphasizes the significance of digital technology in expanding market share and enhancing the competitiveness of hydroponic micro, small, and medium-sized enterprises (MSMEs) through the use of innovative and effective e-commerce platforms.